In vivo veritas, in vitro artificia - Matarese, Giuseppe (2012)
Recently, the understanding of dynamic cellular changes that occur in vivo has advanced significantly, both at the extracellular and intracellular levels. These changes might fluctuate with daily, circadian, weekly, or monthly intervals, and the approaches used to understand these changing conditions in vitro should parallel in vivo studies. In addition, the in vitro milieu should be optimized and better defined, so that artefacts due to in vitro culture systems would not pose dangers for the proper interpretation of results. In this article, we discuss some of these issues and propose solutions.